PENGARUH PARTISIPASI ANGGARAN DAN GOOD GOVERNANCE TERHADAP KINERJA PEMERINTAH DAERAH (STUDI PADA DINAS KESEHATAN KOTA KENDARI) - Intihanah, Intihanah; Muthia, Nur Afifa (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACT This study aimed to examine the effect of the Budget Participation and Good Governance on the Performance of Local Government in the Health Department Kendari. The population are used in this study that all employees at the Department of Health Kendari amounted to 93 people, where the number of samples amounted to 32 people. The samples in this study using purposive sampling technique. Data analysis method used is multiple linear regression test such as t test and F test with used computer program SPSS 20 for windows.The result of this study show that in partially, budgetary participation and good governance have a positive and significant effect on the performance of local government on Health Department Kendari. In simultaneously, independent variables namely budgetary participation and good governance have a significant effect on the performance of local government on Health Department Kendari. Coefficient determination test showed the value of R Square of 0.391, this shows that the ability of independent variables in explaining the dependent variable is quite good with the coefficient of determination of 39.1%, while the remaining 60.9% is explained by other variables not examined.Keywords: Budgetary Participation, Good Governance, and Performance of Local Government.